Accounting knowledge: Does it strengthen application acceptability in BUMDes financial reporting in Pemalang Regency? - Ratieh Widhiastuti; Fadilla Julia Rossa (International Journal of Academe and Industry Research, 2025)
This study aims to analyze the use of Excel macro applications by Village-owned enterprise/Badan Usaha Milik Desa (BUMDes) managers in Pemalang Regency based on the TAM theory by adding accounting knowledge variables as mediation. This study uses a quantitative approach. The study population was 126 BUMDes managers. The data collection technique used a questionnaire. The data analysis technique used descriptive statistics and path analysis. The results of the descriptive analysis showed that the behavioral intention and accounting knowledge variables were in the high category, the perceived usefulness variable was in the helpful category, the perceived ease of use variable was in the easy category, and the attitude of use variable was in the good category. The results showed that perceived usefulness, perceived ease of use, and attitude of use positively affected behavioral intention. Perceived usefulness and perceived ease of use positively affected the attitude of use. Attitude of use did not mediate the effect of perceived usefulness on behavioral intention, but mediated the impact of perceived ease of use on behavioral intention. Surprisingly, results found that accounting knowledge increasingly weakens the attitude of BUMDes managers to use the Excel Macro application. Different business characteristics cause BUMDes' financial managers with an accounting background to not immediately accept new applications for preparing financial reports. Based on the results obtained, the study suggests that the Community and Village Empowerment Service of Pemalang Regency promotes socialization to increase BUMDes managers' intention to understand the ease and benefits of the Excel macro application and increasingly more active in providing training on the use of applications.